PENGARUH KREATIVITAS DAN INTERAKSI GURU DALAM PEMBELAJARAN TERHADAP MINAT BELAJAR SISWA DI MASA PANDEMI COVID-19 DI SMKN 2 KURIPAN TAHUN PELAJARAN 2020/2021 - Ahmad Muslim; Nadya Restu Amanda; Muhammad Iqbal (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2021)
This study aimsat determine how the teacher creativity and interaction in learning effects on student interest in learning during the Covid-19 pandemic at State Vocational High School 2 KuripanAcademic Year 2020/2021. The research method used by the researcher was 1) the sample used in this study was 100 students, 2) the data collection method used was the questionnaire and documentation method, then 3) the data analysis technique used was descriptive statistics and multiple regression analysis, conducted using SPSS 16 software. The results of data analysis shows that: 1) There was a positive influence on teacher creativity in learning on student interest in learning during the Covid-19 pandemic, based on the significance level of teacher creativity (X1) 0.000 <0.05, and the value of t-count 3.805 that is greater than t-table 1.984; 2) There is a significant effect of teacher learning interaction on student interest in learning during the Covid-19 pandemic, based on significance level of teacher interaction (X2)0.008 <0.05, and the t-count value of 2.719 greater than t-table 1.984;and 3) There is a significant effect of teacher creativity and interaction in learning on student learning interest during the Covid-19 pandemic with an F-count value of 15.213 that is higher than the value of F-table 3.09. Based on the results of the analysis, all Ha-s are accepted. Finally, it can be concluded that teacher creativity and interaction in learning have a significant effect both partially and simultaneously onstudent interest in the Covid-19 pandemic at State Vocational High School 2 Kuripan Academic Year 2020/2021. Keywords: Teacher Creativity, Student Learning Interest